Srikandi is a Man: Representations of Sex, Gender, and Sexual Orientation in Hikayat Pandawa - Arezha, Salma; Wirajaya, Asep Yudha (Buana Gender: Jurnal Studi Gender dan Anak, 2026)
Indonesians know Srikandi as a strong woman who married Arjuna. However, in the original Mahabharata story, Arjuna never married Srikandi, but instead married her sister, Drupadi. This is interesting to study in order to understand the reasons behind the differences between the two versions. This descriptive qualitative study aims to re-examine the perception of Srikandi as a woman and describe the representation of sex, gender, and sexual orientation of the character Srikandi in the original Hikayat Pandawa. It was found that in the Mahabharata, Srikandi is not only a woman, but has a complex sexual identity, gender, and sexual orientation. She was born as a woman and grew up with masculine behaviour. As a teenager, Srikandi was attracted to Dewi Nilawati, so she decided to marry a feminine woman and change her gender to male. Srikandi met Begawan Binun to change his sex. Therefore, it can be concluded that Srikandi is actually an LGBTQ representative in the Mahabharata story. Srikandi is not a woman in the end, so it is not appropriate to consider Srikandi as a symbol of women's empowerment today in Indonesia. Srikandi's identity was deliberately covered up by the cultural influence of the Javanese empire in the 12th-13th centuries, as well as the transition of Indonesian society from Hindu-Buddhist to Islam.